Multicentre translational Trial of Remote Ischaemic Conditioning in Acute Ischaemic Stroke (TRICS): protocol of multicentre, parallel group, randomised, preclinical trial in female and male rat and mouse from the Italian Stroke Organization (ISO) Basic Science network. Issue 1 (24th November 2020) - Tettamanti, Mauro; Beretta, Simone; Pignataro, Giuseppe; Fumagalli, Stefano; Perego, Carlo; Sironi, Luigi; Pedata, Felicita; Amantea, Diana; Bacigaluppi, Marco; Vinciguerra, Antonio; Valente, Alessia; Diamanti, Susanna; et al.
Abstract : Introduction: Multicentre preclinical randomised controlled trials (pRCT) are emerging as a necessary step to confirm efficacy and improve translation into the clinic. The aim of this project is to perform two multicentre pRCTs (one in rats and one in mice) to investigate the efficacy of remote ischaemic conditioning (RIC) in an experimental model of severe ischaemic stroke. Methods and analysis: Seven research laboratories within the Italian Stroke Organization (ISO) Basic Science network will participate in the study. Transient endovascular occlusion of the proximal right middle cerebral artery will be performed in two species (rats and mice) and in both sexes. Animals will be randomised to receive RIC by transient surgical occlusion of the right femoral artery, or sham surgery, after reperfusion. Blinded outcome assessment will be performed for dichotomised functional neuroscore (primary endpoint) and infarct volume (secondary endpoint) at 48 hours. A sample size of 80 animals per species will yield 82% power to detect a significant difference of 30% in the primary outcome in both pRCTs. Analyses will be performed in a blind status and according to an intention-to-treat paradigm. The results of this study will provide robust, translationally oriented, high-quality evidence on the efficacy of RIC in multiple species of rodents with large ischaemic stroke. Ethics and dissemination: This is approved by the Animal Welfare Regulatory Body of the University of Milano Bicocca, under project license from the Italian Ministry of Health. Trial results will be subject to publication according to the definition of the outcome presented in this protocol. Trial registration number: PCTE0000177.